2021
DOI: 10.1002/art.41656
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for COVID‐19 and Rheumatic Disease Flare in a US Cohort of Latino Patients

Abstract: Objectives Latino patients are overrepresented among cases of coronavirus disease 2019 (COVID‐19) and are at an increased risk for severe disease. Prevalence of COVID‐19 in Latinos with rheumatic diseases are poorly reported. The purpose of this study was to characterize COVID‐19 clinical features and outcomes in Latino patients with rheumatic diseases. Methods This is a retrospective study of Latino patients with rheumatic diseases from an existing observational cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…COVID-19 vaccine and SARS-CoV-2 infection partly shared mechanisms for triggering RD relapse ( 7 , 8 ). As shown above, the vaccine showed no direct association with flare, while SARS-CoV-2 infection was reported as an independent risk factor for RD flare in some studies ( 52 54 ). The flare rate of RD after SARS-CoV-2 infection presented a vastly higher flare risk than that after vaccination ( 52 58 ), with most flare rates being higher than 20% and some even higher than 40%.…”
Section: The Flare Risk After Sars-cov-2 Infection Compared To the Fl...mentioning
confidence: 82%
See 1 more Smart Citation
“…COVID-19 vaccine and SARS-CoV-2 infection partly shared mechanisms for triggering RD relapse ( 7 , 8 ). As shown above, the vaccine showed no direct association with flare, while SARS-CoV-2 infection was reported as an independent risk factor for RD flare in some studies ( 52 54 ). The flare rate of RD after SARS-CoV-2 infection presented a vastly higher flare risk than that after vaccination ( 52 58 ), with most flare rates being higher than 20% and some even higher than 40%.…”
Section: The Flare Risk After Sars-cov-2 Infection Compared To the Fl...mentioning
confidence: 82%
“…As shown above, the vaccine showed no direct association with flare, while SARS-CoV-2 infection was reported as an independent risk factor for RD flare in some studies (52)(53)(54). The flare rate of RD after SARS-CoV-2 infection presented a vastly higher flare risk than that after vaccination (52)(53)(54)(55)(56)(57)(58), with most flare rates being higher than 20% and some even higher than 40%. This may also encourage RD patients to receive the COVID-19 vaccination.…”
Section: The Flare Risk After Sars-cov-2 Infection Compared To the Fl...mentioning
confidence: 87%
“…One USA-based, prospective study assessed the association of SARS-CoV-2 infection with development of a disease flare in Latin-American patients with RMDs, reporting an increased risk (OR 4.57, 95% CI 1.2 to 17.4). 9 One US-based, retrospective study in the TriNetX database compared outcomes of matched patients with inflammatory RMDs and COVID-19 in the early (January-April 2020) and late (April-July 2020) phases of the pandemic. 51 The study showed that patients with COVID-19 in the late cohort fared better than those in the early cohort, based on lower risk of COVID-19-related hospitalisation (RR 0.…”
Section: Other Outcomesmentioning
confidence: 99%
“…Flares of SLE in patients with COVID-19 have been described [46]. A study in a cohort of Hispanic COVID-19 patients from United States with rheumatic diseases identified COVID-19 positivity as a risk factor for disease flares [47]. To date, we have not found publications reporting cases of relapses of previous controlled IgA vasculitis associated with COVID-19.…”
Section: Discussionmentioning
confidence: 82%